The Utility of the Pandemic Grief Scale in Identifying Functional Impairment from COVID-19 Bereavement. - Lee, Sherman A; Neimeyer, Robert A; Breen, Lauren (2021)
Background: Meeting the needs of people bereaved by COVID-19 poses a substantial challenge to palliative care. The Pandemic Grief Scale (PGS) is a 5-item mental health screener to identify probable cases of dysfunctional grief during the pandemic. Objective: The PGS has strong psychometric and diagnostic features. The objective was to examine the incremental validity of the PGS in identifying mourners at risk of harmful outcomes. Design: A cross-sectional survey design involving sociodemographic questions and self-report measures of pandemic grief, generalized anxiety, depression, post-traumatic stress, separation distress, functional impairment, meaning-making difficulties, and substance use coping. Setting/Subjects: A sample of people bereaved through COVID-19 (N = 1065) in the United States. Results: Fully 56.6% of participants scored above the cut score of ≥7 on the PGS for clinically dysfunctional pandemic grief and 69.7% coped with their loss using drugs or alcohol for at least several days in past two weeks. PGS scores were not associated with time since loss. Hierarchical multiple regression models demonstrated that the PGS uniquely explained variance in functional impairment, meaning-making difficulties, and substance use coping, over relevant background factors, bereavement-related psychopathology, and separation distress. In the final model, the standardized regression coefficients for the PGS were 2-15 times larger than for the other competing measures in explaining each of the three outcomes. Conclusions: The findings underscore the clinical utility of this short and easy-to-use measure in identifying risk of deleterious outcomes across a range of functional and behavioral domains.